Possible Role of Mitochondrial Transfer RNA Gene 5816 A > G Genetic Polymorphism (m.5816A > G) in a 3-Year-Old Child with Dystonia: Report of a Case - Wang, Sumei; Liang, Minglu; Ma, Jiehui; Huang, Sheng; Fan, Lili; Zhu, Feng; Sun, Dan (Global Medical Genetics, 2023)
Background Mutations in the mitochondrial transfer RNA (mt-tRNA) gene are a hotspot for mitochondrial DNA (mtDNA) mutations and are most common in mitochondrial diseases.Methods We identified the mt-tRNA gene 5816 A > G (m.5816 A > G) mutation in a 3-year-old child with dystonia who died. We performed clinical evaluation, genetic analysis, and biochemical investigation with mitochondrial function testing.Results Our patient was found to have dystonia with hyperlactatemia. Electroencephalogram findings were abnormal in children with numerous multifocal spikes, multispike, spikes and slow waves, slow waves and low amplitude fast waves, more pronounced in the occipital region bilaterally, and occurring continuously during sleep. One year later, the preexisting patient had seizures lasting 1 to 2 hours and subsequently died. mtDNA sequencing revealed that the proband, her mother, and her grandmother all carried the m.5816A > G mutation. Oxygen consumption rate (OCR) assays revealed that the proband's basal resting OCR, adenosine triphosphate production, proton leak, maximal respiration, and spare capacity OCR were all significantly lower compared with healthy children of the same age.Conclusion The present case demonstrates a childhood dystonia caused by a mt-tRNA gene 5816 A > G mutation, which has never been reported before. Our findings provide valuable new insights into the pathogenic mechanism and function of the m.5816A > G mutation.
Keywords: mitochondrial DNA mutation; mitochondrial diseases; dystonia; epilepsy